Actions By KPI As A Supervisory Institution Against Advertisements That Violate Ethics - Sherly Angelina; Dwi Desi Yayi Tarina (Syiah Kuala Law Journal, 2022)
Advertising is a tool used by business actors to promote their products. Advertisements must contain complete, correct, clear, and honest information regarding the product. Moreover, advertisement must follow broadcastiong ethics. The broadcasting ethics are listed in Law Number 32 of 2002 concerning Broadcasting, KPI Regulation Number 01/P/KPI/03/2012 concerning Broadcasting Behavior Guidelines, KPI Regulation Number 02/P/KPI/03/2012 concerning Broadcast Program Standards, and Advertising Ethics Indonesia.  However globalization causes rapid developments in the digital world that resulting in advertising often violating broadcasting ethics. The purpose of this study is to explain the supervisory function carried out by KPI and analyze KPI’s actions against advertisements thay violate ethics. The research method used is emperical juridical with a statutory approach and a case approach. The result is supervision carried out by KPI, namely by monitoring every advertisement that is being broadcast and if it is found or there is a report on advertisements that violate ethics, administrative sanctions will be given in accordance with the decision of the 9 (nine) Commissioners on Plenary Meeting.